Bridging Psak 69 And Smallholder Plantation Accounting: Fair Value Constraints And Simplified Reporting - Fredrik Bastian Kawani; Novi Maryam Lempao; Feliks Arfid Guampe (International Journal of Economics, Management and Accounting, 2026)
The gap between PSAK 69, which requires biological assets to be measured using fair value, and accounting practices in Indonesian smallholder plantations indicates significant implementation constraints, particularly in relation to data availability, recording capacity, and market conditions. This study aims to systematically synthesize the literature to identify the main barriers to PSAK 69 implementation and to formulate a simplified and contextual reporting design. The study employs a Systematic Literature Review (SLR) guided by the PRISMA 2020 framework. Literature was retrieved from Scopus, Google Scholar, Garuda, SINTA, and Neliti. Articles were selected using predefined inclusion criteria, namely publication between 2014 and 2026, written in Indonesian or English, available in full text or with complete metadata, and relevant to PSAK 69 and biological assets. Of the 210 records initially identified, 40 articles were included in the final synthesis. The selected studies were analyzed using thematic analysis. The findings indicate that fair value constraints are associated with inactive markets, price volatility, proxy pricing, and high appraisal costs. These constraints are reinforced by limited biological data and weak recording capacity among small-scale actors. Institutional support also plays an important role in facilitating data availability and improving reporting quality. Based on these findings, this study proposes a tiered simplified reporting model as an implementable approach to bridge PSAK 69 requirements and accounting practices in smallholder plantations in a gradual and contextual manner.